2015
DOI: 10.5796/electrochemistry.83.670
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progresses of Electrochemical Surface Science ∼Importance of Surface Imaging with Atomic Scale∼

Abstract: In the electrochemical surface science during the past 20 years, in-situ electrochemical scanning tunneling microscopy (EC-STM) and atomic force microscopy (AFM) have made significant contribution to understand various electrochemical processes with atomic scale. For examples, the underpotential deposition of copper, silver, and other metal ions; the specific adsorption of anions such as iodine and sulfate/bisulfate ions; electrochemical etching processes of metals and semiconductors and the molecular assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Combined LEED, TDS and IRAS analysis showed that the co-adsorbed layer forms a (3×7) ordered structure of bisulfate (HSO4 -), as also found in situ in sulfate-containing electrolytes on closed-packed (111)-oriented Au [18][19][20][21][22], Pt [23], Rh [24], Ir [25], Pd [26], Cu [27] and Ru(0001) [28], with at least 2 water bonded molecules (H2O and H3O + ). Subsequent temperature increase/decrease reversibly converted the (3×7) structure in a (3×3) structure of neutral H2SO4 by desorption/re-adsorption of water.…”
Section: Bridging the "Immersion Gap"mentioning
confidence: 67%
“…Combined LEED, TDS and IRAS analysis showed that the co-adsorbed layer forms a (3×7) ordered structure of bisulfate (HSO4 -), as also found in situ in sulfate-containing electrolytes on closed-packed (111)-oriented Au [18][19][20][21][22], Pt [23], Rh [24], Ir [25], Pd [26], Cu [27] and Ru(0001) [28], with at least 2 water bonded molecules (H2O and H3O + ). Subsequent temperature increase/decrease reversibly converted the (3×7) structure in a (3×3) structure of neutral H2SO4 by desorption/re-adsorption of water.…”
Section: Bridging the "Immersion Gap"mentioning
confidence: 67%
“…In‐situ microscopic imaging of electrochemical processes helps reveal the nature of key elementary steps and relevant structures that occur on electrode surfaces and are generally averaged over the whole surface when using macroscopic techniques. There has been considerable progress in investigating the assembly of oxoanions at solid‐electrolyte interfaces with in‐situ scanning tunnelling microscopy (STM) . Nevertheless, only a few studies are found on the adsorption behaviour of two‐oxygen oxoanions, in contrast to those found for three‐ and four‐oxygen oxoanions …”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable progress in investigating the assembly of oxoanions at solid-electrolyte interfaces with in-situ scanning tunnelling microscopy (STM). [1,[14][15][16][17][19][20][21][22] Nevertheless, only a few studies are found on the adsorption behaviour of two-oxygen oxoanions, [23][24][25] in contrast to those found for three-and four-oxygen oxoanions. [16,17,19,[26][27][28] Acetate and formate represent the simplest examples of carboxylates (anions of carboxylic acids), which are a major group of molecular species that strongly adsorb on catalytically active noble metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…As a complementary characterization, the local morphology and the crystal structure can be explored by EC-scanning tunneling microscopy (EC-STM) 9,10,11,12,13,14 , possibly achieving an atomic resolution imaging of the surface morphology. This set-up has been rarely applied to the case of anions intercalation 15,16,17 , where the crystal surface is heavily modified and the high perturbing faradaic currents, flowing through the surface, make the EC-STM an uncommon technique for this kind of investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Answering these questions can prove useful for further improvement and optimization of chemical exfoliation processes, tuning the local surface dynamics at the first stages of anion intercalation. As a complementary characterization, local morphology and crystal structure can be explored by electrochemical scanning tunneling microscopy (EC-STM), possibly achieving atomic resolution imaging of the surface morphology. This setup has been rarely applied to the case of anion intercalation, where the crystal surface is heavily modified and the high perturbing faradaic currents, flowing through the surface, make EC-STM an uncommon technique for this kind of investigation.…”
Section: Introductionmentioning
confidence: 99%